2012
DOI: 10.5194/acp-12-6041-2012
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide and related trace gases and aerosols over the Amazon Basin during the wet and dry seasons

Abstract: Abstract. We present the results of airborne measurements of carbon monoxide (CO) and aerosol particle number concentration (CN) made during the Balanço Atmosférico Regional de Carbono na Amazônia (BARCA) program. The primary goal of BARCA is to address the question of basinscale sources and sinks of CO 2 and other atmospheric carbon species, a central issue of the Large-scale BiosphereAtmosphere (LBA) program. The experiment consisted of two aircraft campaigns during November-December 2008 (BARCA-A) and May-J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(142 citation statements)
references
References 118 publications
(129 reference statements)
7
124
0
11
Order By: Relevance
“…The pollution markers cCO and MBCe in Fig. 1a show a pronounced seasonal cycle with a prevalence of clean conditions in the wet season vs. the biomass burning-related pollution maximum in the dry season (Andreae et al, 2015 (Martin et al, 2010b;Andreae et al, 2012;2015). Similar to the MBCe trends, the total aerosol particle concentration NCN, 10 …”
Section: Aerosol and Cloud Microphysical Seasonality In The Amazonsupporting
confidence: 54%
See 1 more Smart Citation
“…The pollution markers cCO and MBCe in Fig. 1a show a pronounced seasonal cycle with a prevalence of clean conditions in the wet season vs. the biomass burning-related pollution maximum in the dry season (Andreae et al, 2015 (Martin et al, 2010b;Andreae et al, 2012;2015). Similar to the MBCe trends, the total aerosol particle concentration NCN, 10 …”
Section: Aerosol and Cloud Microphysical Seasonality In The Amazonsupporting
confidence: 54%
“…), in contrast to much higher ΔNCN,10/ΔcCO levels for urban (100 -300 cm -3 ppb -1 ) and power plant emissions (up to 900 cm -3 ppb -1 ) (Janhaell et al, 2010;Kuhn et al, 2010; 15 Andreae et al, 2012). Furthermore, the ratios of excess NCCN(S) to excess cCO, ΔNCCN(S)/ΔcCO, for the individual S levels range between 6.7 ± 0.5 cm -3 ppb -1 for the lowest S = 0.11 % and values around 18.0 ± 1.3 cm -3 ppb -1 for higher S (see Table S1 and ), 'swamping' the Aitken mode DAit = 70 ± 1 nm, NAit = ~140 cm -3 ) almost completely, giving the entire distribution a monomodal appearance.…”
mentioning
confidence: 99%
“…This pattern is probably related to the 20 km model resolution not picking up individual biomass burning plumes and fire emission underestimation (Pereira et al, 2016). Previous studies indicated that biomass burning emissions contribute more than 95 % to the variability of CO over the Amazon and that the emissions used in this study (3BEM; Longo et al, 2010) are about 20 % underestimated (Andreae et al, 2012).…”
Section: Smoke Regional Plume Co and Co 2 Mixing Ratiosmentioning
confidence: 80%
“…There was an enhancement of CO from July to October for both years in all four locations. In 2010, the CO mixing ratio values in the PBL during the dry season increased from 100 to 150 ppb, which are typical wet season values (Andreae et al, 2012), to up to 500 ppb in both the simulations and observations. The dry season of 2010 had CO mixing ratios about twice as high as the same period in 2011; this is consistent with the total number of fires, which approximately doubled, detected by remote sensing during the dry season of these two years (http://www.inpe.br/queimadas/estatisticas.php).…”
Section: Smoke Regional Plume Co and Co 2 Mixing Ratiosmentioning
confidence: 91%
“…4a, show a decreasing dominance of ESE winds from August to November, whereas from October to November there is an increasing influence of ENE winds, indicating the south-to-north air mass trajectory shift that occurs during the transition from the dry to the wet season. It is important to note that southerly and easterly winds are most likely to bring BB aerosol to the ATTO site during the dry season, given that very active open fire areas during this period are located in the southern Amazon and the Cerrado region (Andreae et al, 2012;Guyon et al, 2005) and, more remotely, in southern Africa (Andreae et al, 1994;Barbosa et al, 1999;Das et al, 2017). Aerosol optical depth at 550 nm is used in this study as a parameter to study the seasonal pattern of BB emission transport from both areas.…”
Section: Variability Of Optical Properties During the Dry Seasonmentioning
confidence: 99%